Content, Cause, and Consequences of Job Insecurity: A Theory-Based Measure and Substantive Test - Ashford, Susan J.; Lee, Cynthia; Bobko, Phillip (Academy of Management Journal, 1989)
This research assessed the causes and consequences of job insecurity using a new theory-based measure incorporating recent conceptual arguments. We also compared the measure's reliability and construct validity to those of two existing global measures of job insecurity. Results indicated that personal, job, and organizational realities associated with a perceived lack of control are correlated with measured job insecurity. Job insecurity in turn leads to attitudinal reactions-intentions to quit, reduced commitment, and reduced satisfaction. These results generally support the utility of our new measure and provide important directions for future research.